Ethnological Studies on Visiting Traditions for Preservation Community Culture - Casminih, Casminih (Indonesian Journal of Adult and Community Education, 2023)
The tradition is hereditary customs of ancestor that still maintained his presence in the community. One of the traditions of the societies in Indramayu Regency is called "Unjungan". The purpose of this study is to describe the implementation of the Unjungan Tradition, to analyze the values of the Unjungan Tradition implementation and to find the impact/influence to the surrounding community in Indramayu Regency. Based on the results of the study, it was found that: a) Unjungan were held at cemeteries where there were graves of community leaders, historical figures or local regional heroes accompanied by regional arts titles, b) there were religious, social and moral values in the implementation of Unjungan tradition, c) there was economic improvement for the local community. Referring to the results of this study, it means that the Unjungan Tradition is a local culture that must be maintained and there needs to be support from the local government of Indramayu Regency to assist the community in socializing it to audiences inside and outside Indramayu Regency.